3D-FDTD Method for Analysis of Rectangular Waveguide Loaded with Anisotropic Dielectric Material - Maulana Randa; Achmad Munir (IAES Indonesia Section, 2014)
One of the most popular techniques to solve electromagneticproblems numerically is using finite-difference timedomain(FDTD) method. The method has been successfullyapplied to an extremely wide variety of electromagnetic problems.The essential reason resides in the fact that the FDTD methoditself is extremely simple even for analyzing in a three-dimensional(3D) system. In this paper, the analysis of resonant frequencyfor a rectangular waveguide which is loaded with anisotropicdielectric material is numerically investigated based on 3D-FDTDmethod. The wave equations and modes that appear in thewaveguide are analyzed theoretically in which the results areapplied to validate the numerical result obtained from 3D-FDTDmethod. For comparison, an empty rectangular waveguide anda rectangular waveguide fully loaded with isotropic dielectricmaterial are also analyzed both theoretically and numerically.From the result, it shows that a good agreement has been achievedbetween theoretical calculation and 3D-FDTD numerical resultswith their discrepancies of 0.26–2.32%.